Interdisciplinary relationships between Health Education and Universal Literature - Míriam Gutiérrez Escobar; Felicia Margarita Llerena Bermúdez; Lourdes González Pérez; José Carlos Medina Alejo; María Bello Benet; Anisley Cazañas Hernández (Medisur)
It is uncommon that literary work is used to reflect on the healthy lifestyles of men, since that is not an objective of this artistic branch; however, the literary analysis can serve to value elements that go beyond those Literature Theory studies, such as health education. The objective of this work is to describe the interdisciplinary relatonships which can be stablished between universal literature and Health Education, by means of literary works and teaching guides, in the Technical and Professional Education inserted at the Medical Universities in Cuba, who recieve the subject Spanish-Literature. This is a current imperative originated from the scietific development which education should incorporate to the teaching process. In this way, in addition, the Program for the Health Promotion and Education provided by the Ministries of Education and Health in Cuba is also accomplished. Current and important topics were addressed: collective - personal hygiene and sexual education, by selecting work fragments from different countries and times, from Greco-Latin culture until to the nineteenth century; didactic guides are presented which make it possible to enrich and deepen the study of a work beyond an exclusively literary perspective, contributing to increase health education and strengthen interdisciplinary links. It can be used by professors of the specialty or any other subject which addresses these issues.